2017
DOI: 10.1155/2017/9580209
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Core-Shell PLGA-Chitosan Microparticles Using Electrospinning: Effects of Polymer Concentration

Abstract: This investigation aims to fabricate the core-shell microparticles composed of poly(lactic-co-glycolic acid) and chitosan (PLGA-CS MPs) using electrospinning. The challenge of using electrospinning is that it has many parameters which change product outcome if any single parameter is changed. However, the advantage of this system is that we can fabricate either micro/nanofibers or micro/nanoparticles. To learn about the effect of liquid concentration, the electrospinning parameters (voltage, needle sizes, dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It has been found that if there are many kinds of polymers in the solution, even if the viscosity is the same, different polymer concentration ratio will change the diameter of nanofibers, which is caused by the interaction between polymers [ 113 ]. Some researchers have also changed the solution concentration and prepared microspheres instead of nanofibers by electrospinning, which provides a new idea [ 114 ].
Figure 6 SEM images of electrospun polyimide nanofibers with different concentrations a 10%, b 15% c 20% d 25% [ 105 ].
…”
Section: Parametersmentioning
confidence: 99%
“…It has been found that if there are many kinds of polymers in the solution, even if the viscosity is the same, different polymer concentration ratio will change the diameter of nanofibers, which is caused by the interaction between polymers [ 113 ]. Some researchers have also changed the solution concentration and prepared microspheres instead of nanofibers by electrospinning, which provides a new idea [ 114 ].
Figure 6 SEM images of electrospun polyimide nanofibers with different concentrations a 10%, b 15% c 20% d 25% [ 105 ].
…”
Section: Parametersmentioning
confidence: 99%
“…Chitosan has been used as a raw material for the preparation of nanoparticles in recent years, because of their superior properties in nanoscale. With many features such as biocompatibility, biodegradability, membrane adhesion and non-toxicity, chitosan have become the material for many biological pharmacological applications [17,18,19,20,21,22,23,24,25,26,27,28]. In agriculture, chitosan nanoparticles (CSNP) are used as growth promoters for plants [28,29].…”
Section: Introductionmentioning
confidence: 99%